"There is soccer but we have to watch": the embodied consequences of rhetorics of inclusion for South African children with cerebral palsy. (10th January 2015) - Bantjes, Jason; Swartz, Leslie; Conchar, Lauren; Derman, Wayne
ABSTRACT Twenty years after the advent of democracy in South Africa (SA), there have been some successes in the achievement of greater equality, access and inclusion for many persons with disabilities. The move towards inclusive education may, however, have had unanticipated embodied consequences for people positioned discursively as included, but who in fact may in some respects be further marginalised than they had been under apartheid. We describe ethnographic research conducted in a special needs school in SA to explore the lived experiences of children with cerebral palsy and their involvement in physical activity. Our study shows how inclusive educational practices in SA have impeded involvement in sport for some children with motor impairments because of resource limitations and other historic reasons. This paper raises important questions about the role of community psychology in recognising, naming and contributing to action around injustices, which may be hard to see but which can have profound effects on the lives and bodies of those who experience exclusion. Copyright © 2015 John Wiley & Sons, Ltd.